Multiple etiologies of axonal sensory motor polyneuropathy in a renal transplant recipient: a case report - Etemadi, Jalal (BioMed Central, 2011)
INTRODUCTION: Neurological complications leading to morbidity and mortality are not frequent in renal transplant recipients. Here, we report a renal transplant recipient who presented with diminished strength in his limbs probably due to multiple etiologies of axonal sensorimotor polyneuropathy, which resolved with intravenous immunoglobulin. CASE PRESENTATION: A 49-year-old Iranian male renal transplant recipient with previous history of autosomal dominant polycystic kidney disease presented with diminished strength in his limbs one month after surgery. Our patient was on cyclosporine A, mycophenolate mofetil and prednisone. Although a detected hypophosphatemia was corrected with supplemental phosphate, the loss of strength was still slowly progressive and diffuse muscular atrophy was remarkable in his trunk, upper limb and pelvic girdle. Meanwhile, his cranial nerves were intact. Post-transplant diabetes mellitus was diagnosed and insulin therapy was initiated. In addition, as a high serum cyclosporine level was detected, the dose of cyclosporine was reduced. Our patient was also put on intravenous ganciclovir due to positive serum cytomegalovirus immunoglobulin M antibody. Despite the reduction of oral cyclosporine dose along with medical therapy for the cytomegalovirus infection and diabetes mellitus, his muscular weakness and atrophy did not improve. One week after administration of intravenous immunoglobulin, a significant improvement was noted in his muscular weakness. CONCLUSION: A remarkable response to intravenous immunoglobulin is compatible with an immunological basis for the present condition (post-transplant polyneuropathy). In cases of post-transplant polyneuropathy with a high clinical suspicion of immunological origin, administration of intravenous immunoglobulin may be recommended.